Impact of initial lipid content and oxygen supply on alcoholic fermentation in champagne-like musts. (August 2017) - Ochando, Thomas; Mouret, Jean-Roch; Humbert-Goffard, Anne; Sablayrolles, Jean-Marie; Farines, Vincent
Abstract: Available nitrogen, lipids, or oxygen are nutrients with major impact on the kinetics of winemaking fermentation. Assimilable nitrogen is usually the growth-limiting nutrient which availability determines the fermentation rate and therefore the fermentation duration. In some particular cases, as in Champagne, grape musts have high available nitrogen content and low turbidity, i.e., below 50 Nephelometric Turbidity Unit (NTU). In the case of low turbidity, the availability of lipids, particularly phytosterols, becomes limiting. In this situation, control of oxygenation, which is necessary for lipid synthesis by yeast, is particularly crucial during fermentation. To mimic and understand these situations, a synthetic medium simulating the average composition of a Champagne must was used. This medium contained phytosterol (mainly β-sitosterol) concentrations ranging from 0 to 8 mg/L corresponding to turbidity between 10 and 90 NTU. Population reached during the stationary phase and the maximum fermentation rate are conditioned by the initial phytosterol concentration determining the amount of nitrogen consumption. An early loss of viability was observed when the lipid concentrations were very low. For example, the viability continuously decreased during the stationary phase to a final value of 50% for an initial phytosterol concentration of 1 mg/L. In some fermentations, 10 mg/L oxygen were added at the end of the growth phase to combine the effects of initial content of phytosterols in the musts and the de novo synthesis of ergosterol and unsaturated fatty acids induced by oxygen addition. Effect of oxygen supply on the fermentation kinetics was particularly significant for media with low phytosterol contents. For example, the maximum fermentation rate was increased by 1.4-fold and the fermentation time was 70 h shorter with oxygen addition in the medium containing 2 mg/L of phytosterols. As a consequence of the oxygen supply, for the media containing 3, 5 and 8 mg/L of phytosterols, the assimilable nitrogen was completely exhausted and the fermentation kinetics, as well as the final populations and viabilities (greater than 90%), were identical for the 3 conditions. The impacts of the lipid content and additional oxygen on acetate, glycerol and succinate synthesis were also studied. The phytosterols decreased the acetate and increased the succinate synthesis, and oxygenation resulted in a decrease in succinate formation. This work highlights the similarities and differences between the effects of lipids and oxygen on fermentation kinetics and yeast metabolism. This research highlights the need for an optimal combined management of lipid content in the must via turbidity and oxygenation, particularly in nitrogen-rich musts. Graphical abstract: Highlights: Nitrogen–lipids balance in champagne musts induce fermentation limited by lipids. Lipids availability determines kinetics parameters and organoleptic wine profile. Combined management of turbidity and oxygen allows solving lipid deficiency.